EQUILIBRIUM GARNET-CALCITE OXYGEN ISOTOPE FRACTIONATION - Rosenbaum J.M.; Mattey D. (My University, 1995)
The equilibrium oxygen isotope fractionation between grossular/andradite garnet and calcite has been determined experimentally by direct exchange from 800-1200°C at ~23 kbar. A least-squares fit to the equilibrium fractionation data reflected through the origin has the functional form 1000 1n αT(K)gr-ct = (?2.77 +/- 0.19) ? 106/T2 + (0.0 +/- 0.13) for temperatures greater than 800°C (+/-2σ errors). This is in good agreement with the difference between the reduced partition function ratios of the two phases recalculated for the purpose of comparison. The temperature coefficient from the experimental data curve has been combined with those of previous mineralcalcite exchange experiments to produce an internally consistent set of garnet-mineral oxygen isotope geothermometers.